Simulations of Photodegradation of Toluene and Formaldehyde in a Monolith Reactor Using Computational Fluid Dynamics - Chong, Siewhui; Wang, Shaobin; Tade, Moses; Ang, Ha Ming; Pareek, Vishnu (American Institute of Chemical Engineers., 2011)
In this study, simulations were conducted on a monolith reactor for the photodegradation of toluene and formaldehyde. The monoliths in the reactor were treated as porous zones and the photocatalytic oxidation occurring on the monolith surfaces was modeled using Langmuir–Hinshelwood kinetics. A discrete ordinates model was used to simulate the light intensity with a novel approach, which involved an adjustable parameter—the absorption coefficient of the channel wall, for modeling the local light intensity across the porous media. The advantage of this approach was that despite its simplicity, it was able to capture and visualize the local light profile across the monolith channels and to integrate it into the reaction kinetics. Although it required a trial-and-error to determine the correct value of the channel wall absorption coefficient, the proposed model achieved a reasonable agreement between the simulation results and published experimental data.